PEMBELAJARAN MENARI PADA KELOMPOK TARI ANAK USIA SEKOLAH DASAR - Yuniar, Devi; Julia, Julia; Gusrayani, Diah (Jurnal Pena Ilmiah, 2017)
Dancing learning as part of art learning is a great contribution to improving the creativity of primary school aged children. The importance of dance learning is to prepare the child's condition to be able to channel his talents and creativity which will then culminate in a growing achievement of each child in a dance group. Primary school-aged children who follow the learning in the studio have the opportunity to master dancing skills. It is a creativity to preserve culture through the manifestation of beautiful movement. Case studies were selected as research designs that aimed to investigate and track the learning process of dance groups in the studio. Technique used in this research that is observation, interview, and field note, so that obtained data which give picture about dance learning which done. This research is done in studio Dwi Arta Production Ciwidey, Regency of South Bandung. Based on the research conducted, obtained some findings related to the description of dance learning process of dance groups of elementary school age children.